Android Tips And Trick for dummy - Rosari J (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2019)
Android is a highly strong and innovative mobile operating system that frequently outperforms Apple's iOS in terms of support for new technology. The list goes on and on: 5G, NFC payment, bespoke keyboards, and so on. However, all of that cutting-edge capabilities results in a complex, huge operating system. The UI appears basic enough for casual users—those who just want to text, call, and use their apps—but there are a number of power-user settings and capabilities hidden a layer or two down in the interface. All you have to do is know where to look.We want you to be able to master Google's mobile operating system, and our list of tips and shortcuts can assist you in doing so. These are just a few of the ways you may use Google's OS; there's a long list of things to explore, and you'll undoubtedly discover more. Also, be sure to check out our roundup of the top Android apps, and feel free to leave a comment at the bottom of the page. We may include them in further updates to this storey!1. Remove any apps you don't use. The majority of Android phones come with a large number of preinstalled apps. Many will be appreciated by almost everyone—maps, email, browser, and so on—but there will surely be some that you do not want or want. You don't need a podcast app if you don't listen to podcasts. Furthermore, phone manufacturers frequently add a slew of their own apps that you may never use. Simply press and hold an app's icon for a few seconds, then select the I entry to get to the app's detail page, where you can uninstall it. Unfortunately, certain stock apps are impossible to remove. If you exclusively use Firefox or Edge, for example, you won't be able to delete Google's Chrome browser. You can at the very least select Disable for those apps, which will hide them from the UI and free up system resources.2. Take advantage of digital well-being features Staying up all night messaging and doomscrolling isn't the healthiest thing you can do. The Bedtime mode in Android 11 is part of the Digital Wellbeing feature. It not only silences your phone at a predetermined period, but it also turns the screen black and white in case you need to glance at it after hours. If you need extra time before retiring, select the Pause option in the dropdown menu. If you want more sleep advice, check out our article on how technology can help (or hurt) your sleep. Focus mode, which silences annoying app notifications, is another recommended Wellbeing feature. When you place your phone down with the screen facing down, some phones, like current Pixels and Motorolas, go into Do Not Disturb mode, which is a quick and easy way to get rid of distractions. Finally, when it's time to unwind, Work Profile hides all those productivity apps.3. In Windows, set up your phone app.Android and the Windows 10 Your Phone app I believe that the majority of individuals who use Mac desktops or laptops also use an iPhone, which has excellent interaction with macOS. However, with the Your Phone desktop software for Windows 10, Android users can have just as much—if not more—consistency with their desktop computer. It's easiest to begin the setup process from your computer. Go to the Phone section of the Settings app, select Add a Phone, and you're ready to go. You'll be able to make phone calls, send texts, and see and use photographs from your phone on your PC in real time. With the Link to Windows option, recent Samsung devices and the Surface Duo phone get even more capabilities, including the ability to run numerous Android apps on the desktop under the Your Phone app. You can get Android SMS on the web if you don't have Windows—another feature that Apple's mobile OS doesn't have. You may also use an emulator to run Android apps on Windows or macOS, although this is not as handy as using Windows 10's Your Phone.4. Change the Quick Settings One thing I don't like about Android is that it takes two swipes to reveal more than one row of Quick Settings, and even then, there are two pages of them. In the first swipe-down row, check sure the settings you use the most are there. Simply select the pencil symbol to add essential features such as Focus mode and Dark mode switches.5. Use the Web to Install Apps One of the best features of Android over iOS, in my opinion, is that you don't have to hold your phone in your hand to install an app. You can remotely install any app or game by going to the Google Play store in your web browser, as long as you're signed in to the same Google account as the phone. When you go to install, you'll get a list of your Android devices if you have more than one. It's a terrific time saver if you find an app on your computer and don't want to fiddle with your phone to get it on your phone.6. Download Apps from Other Places One of Android's standout characteristics is that, unlike iOS, you're not limited to using a single app store. The majority of customers will be able to locate any software they desire on Google's Play store, which comes with some useful security features. If you require anything not found there, nothing prevents you from visiting Amazon's app shop, your phone manufacturer's app store, or even downloading and installing the software as an APK (the extension for an Android Application Package file). One thing to keep in mind if you go this route: make sure you download the programme from a reputable source, as third-party app stores are the most common source of Android virus. First, do some research. Also, just in case, switch off the source's Install Unknown Apps feature after you've installed the app you want. The mega-popular game Fortnite is an example of why you would want to sideload (install outside of the official app store) an app. Android users can get the APK from the game developer's website, but iPhone users who wish to install the game for the first time are out of luck. In PCMag's article on how to play Fortnite on Android, you can learn more about the procedure.7. Download and install a launcher app. This is one form of personalization that iPhone owners aren't aware of: you can modify your phone's default start screen by downloading a third-party launcher app from the Play Store. Action Launcher, Apex, the brilliantly called Lawn Chair, Lightning, the Microsoft Launcher, Nova, Niagara, and Smart Launcher are a few notable launchers.Microsoft's Android Launcher Including the iOS 14 launcher, you can even make your Android look like an iPhone, with Siri shortcuts and an App Store icon in place of the Play icon. Do you want to relive the glory days of Windows Phone? There are other launchers that mimic the look and feel of that OS.8. Make Message Notifications Your OwnOptional notifications in Android 11 You can customise your message notifications in Android 11 to make certain contacts stand out more and keep conversations together. You can now have messages appear as bubbles on top of any other active programmes. Simply enable them in Settings and specify the priority of the contact. There's additional setting for Bubbles within a notification, with three options: All Conversations Can Bubble, Selected Conversations Can Bubble, and Nothing Can Bubble.9. Customize Your Home by Adding WidgetsAdd Widgets and Personalize Your Home With iOS 14 comes the option to add widgets to the home screen. For a long time, Android users have been able to accomplish this, but not everyone knows how. Simply long-press on the home screen, select Widgets, and then select from the list of options provided by any apps installed on their phones. Long-pressing on the Home screen also provides you more customization options, such as eliminating the Google feed page from the left side of the screen or disabling screen rotation for the Home screen—which we would never do because it's wonderful to view your home screen in landscape mode.10. Boost StorageAndroid phone with microSD slot One of the biggest advantages of Android over iPhones is that some versions allow you to expand your storage capacity using a microSD card. This not only expands the amount of media and apps you can store on your phone, but it also allows you to transmit vast amounts of data between your phone and other devices. Another advantage is that you can browse the data on some Android phones by plugging them into an external USB storage drive. You may easily plug in a USB flash memory drive with a Type-C connection if your phone has a USB-C port.Antivirus software should be installed. Because Android is significantly more open than iOS—that is, it is more similar to Windows than macOS—it is also far more vulnerable to malware attacks. Although Google has a number of robust security features built in, we recommend that you use an antivirus app on Android. Bitdefender Total Security, Kaspersky Security Cloud, Norton 360 Deluxe, and McAfee AntiVirus Plus are four PCMag Editors' Choice solutions, according to security expert Neil Rubenking. The majority of these also apply to your desktop computers. They make sure you're not installing malicious programmes and run malware scans on a regular basis. They also prevent thieves from gaining access to your phone by simply replacing the SIM card. Some feature VPN protection as well. 12. To open the camera, double-tap the power button. Unlike the iPhone, which has a camera icon on the lock screen, most Android phones allow you to turn on the camera by double tapping the power button. It's critical to have quick camera access to capture such fleeting moments. To focus and take the shot, you can also utilise the volume keys. To record a video, press and hold either button for a long time.13. Make Use Of Screen PinsAndroid's Screen Pinning If you need to pass your phone to someone else and don't want them snooping about in other apps, pin the screen, according to our pals at ExtremeTech.com. You can enable this in the Security menu if it isn't enabled by default. To block them from switching apps, tap the app icon on any programme in the multitasking interface and select "Pin." Switching apps can be secured by needing your phone's PIN. In app switching view, the app icon also allows you to split the screen, pause the app's notifications, and examine its information.14. Establish Guest Access You can give someone else a little more access than what screen-pinning allows. To give someone access to your phone but not to your apps, data, or settings, or to send text messages, go to Settings > System > Advanced > Multiple Users and turn it on. You can enable the Add Users from Lock Screen slider if you want. To access Quick Settings, swipe down twice from the top of your phone. Select Add Guest from your user icon in the lower right corner. The phone takes a few moments to transition to the mode, which disables personal accounts (such as email) but allows you to use the phone, maps, and the internet. You won't have to worry about a guest publishing a Facebook post or tweet for your account because only standard Android apps will appear.15. Keep track of what you do on your computer screen.Android 11 allows you to record your screen. With Android 11, Google included built-in screen-recording functionality. Previously, only Samsung, LG, and OnePlus phones could do so, but now any phone running Android 11 can. It's easy to use: Simply pull down the top shade and select Screen Record > Start Recording from the menu. You can choose whether or not to show touch points and capture sounds. Pull the shade down again and hit the big red bar to stop recording. In our tests, it worked flawlessly, producing a regular MP4 file in the photo gallery.16. Take advantage of developer optionsAndroid Developer Options This one comes from Ben Moore of PCMag. To enable this, go to the About Phone section of the Settings app, scroll down to the Build number, and tap it seven times. Then go to System > Advanced > Developer Options under Settings > System > Advanced > Developer Options. You can reveal screen touches, adjust Bluetooth device options, and set USB connection preferences, as well as a slew of other developer-only options. This is absolutely not for the technophobe, but rather for the hardcore tinker.17. Enable Find My Device.Android's "Find My Device" feature Both mobile OSes contain tools that assist you locate your phone on a map if you misplace it or it is stolen. Not only that, but these Find My services also allow you to disable, wipe, and play a sound on the phone. Apple's mobile operating system goes a step further by allowing you to display your phone number or another message on the screen of a misplaced device, something Google has yet to do.18. Make use of the Battery Saver Mode.Android has a battery saver mode. The Android operating system gives you a lot more control over battery-saving choices than the iPhone. You may use the Adaptive Battery feature, which extends battery life based on your usage patterns, as well as enable Battery Saver mode and have it switch off automatically when the phone is charged. You may also create a timetable for Battery Saver mode to be activated based on your usage or when your battery reaches a certain percentage of charge.19. Use Your Android Phone to Control Your Smart HomeYour Android Phone Can Control Your Smart Home Android version 11 made it easier to control smart home devices. When you hold down the power button for a long time, a screen emerges with large buttons for controlling your light bulbs and other gadgets. To make this work, you'll need to add the devices to the Google Home app and, if desired, establish a room for them.20. Make Regular Updates Our test Pixel's security settings page told us that a security update was available while we were working on this report. You should, without a doubt, install these as soon as feasible. Android updates are easier and faster than ever, and you never know what new features you'll get. Rest assured that we'll keep adding more hacks and shortcuts to this article as we discover them.